Magic and Social Domination in a Rural Turkish Community - Ilcan, Suzan (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1994)
A striking feature of social relations in a northwestern Turkish community occurs in the sphere of moral or religious life. While there are many accounts of religious life in the context of official Islamic doctrine, a wide range of less official beliefs and activities are practised along with formai Islam in the community of Sakli. Magic or büyü designates a range of activities with aims and purposes which do not emanate from the authority of orthodoxy. The value and meaning of büyü is located in attempts to subvert or alter situations that are the product offate, or the actions of more powerful actors. In this context this article illustrates how local villagers take their projects to a hoca (lit. religious teacher) who attempts to shape fate more to their liking, for a fee. In their practice of assisting resistance to what is ’written’ in codes or decided by the powerful, hoca often borrow Qur’anic prayers to support their clients’ projects. Written prayers are used as objects that can effect goals, such as protecting villagers from misfortunes, finding ’appropriate’ mates, casting love spells, and occasionally causing harm. I argue that büyü challenges the collusion between official Islamic authority and mainstream local morality.